A review on functional lung avoidance radiotherapy plan for lung cancer - Yu, Jinhui; Tang, Xiaofeng; Lei, Yifan; Zhang, Zhe; Li, Bo; Bai, Han; Li, Lan (Frontiers in Oncology, 2024)
Lung cancer is the most common malignant tumor in China. Its incidence and mortality rate increase year by year. In the synthesis treatment of lung cancer, radiotherapy (RT) plays a vital role, and radiation-induced lung injury(RILI) has become the major limiting factor in prescription dose escalation. Conventional RT is designed to minimize radiation exposure to healthy lungs without considering the inhomogeneity of lung function, which is significantly non-uniform in most patients. In accordance with the functional and structural heterogeneity of lung tissue, functional lung avoidance RT (FLART) can reduce radiation exposure to functional lung (FL), thus reducing RILI. Meanwhile, a dose-function histogram (DFH) was proposed to describe the dose parameters of the optimized image-guided RT plan. This paper reviews lung function imaging for lung cancer RT plans. It also reviews the clinical applications of function-guided RT plans and their current problems and research directions to provide better guidance for clinical selection.